Forensic Science in the European Union Criminal Justice: the Challenges for Mutual Recognition - JURKA, Raimundas; KURAPKA, Vidmantas Egidijus (Journal of Advanced Research in Law and Economics, 2017)
The main goal of the present article is to identify and disclose, which methodological and practical problems are and may be encountered during the implementation, within the legal practice, of the processes of free movement of evidence across the European Union. The authors highlight the necessity to reveal which structural, institutional, legal and administrative aspects influence the difficulties of implementation of the principle of mutual recognition during the collection and transfer of evidence from one state to another, when such evidence was obtained through the application of the forensic achievements and special knowledge. The absence of the uniform approach towards the use of forensic science for the collection and transfer of evidence to another state due to different quality and methodological standards applied for the provision of forensic services in the international cooperation in criminal proceedings result in the limited efficiency of the principle of mutual recognition. The article applies the systematic analysis, comparative, documentary, critical, logical induction and deduction, abstraction and other research methods, which ensure the methodological, consistent and well-grounded presentation of the analytical reasons, drawing of the conclusions and formulation of the possible solutions for the removal of problems. The authors distinguish two groups of problems, which help identify the difficulties of assessment of the forensic evidence collected and examined in one Member State by the competent judicial authority of another Member State. In particular, those reasons are of the organizational (institutional) nature and of the criminal procedural legal nature. The reasons of the organizational nature require establishment, across the European Union, of uniform and common quality and methodological standards for forensic science laboratories, expert agencies, etc. The reasons of the criminal procedural legal nature show that in order to avoid any difficulties while assessing in court the forensic evidence collected in another Member State, it is necessary to provide a possibility for the requesting state to specify in the request for the collection of the evidence, what formalities must be followed by the executing state in order to secure the admissibility of such evidence.